Inflammatory Dermatoses: The Basics - Smoller, Bruce R. (Springer US : Imprint: Springer, 2010)
Inflammatory Dermatoses: The Basics will serve as an effective and efficient handbook for the student of dermatopathology, and as a practical bench reference for the practicing diagnostician who desires rapid access to criteria that are useful in differentiating histologically similar entities. The chapters consist of essential bullet points arranged in organized outlines allowing for easy access and direct comparison between entities. The elaborate pictorial documentation will also enable the book to serve as an atlas of the most common dermatologic disorders.